Maybe Now A novel - Hoover, Colleen (New York ATRIA paperback, 2022)
The long-awaited finale to the New York Times bestselling Maybe Someday series returns with all the characters you fell in love with.What is more important? Friendship, loyalty, or love?Ridge and Sydney are thrilled to finally be together guilt-free. But
Keywords: Love stories